PEDAGOGICAL PRACTICE WITH DEAF STUDENTS IN ELEMENTARY SCHOOL I - da Silva Dias, Lucinéa (2021)
This article aims to research how the pedagogical practice happens in Elementary School I for deaf students, highlighting the importance of valuing special education and how classroom teachers provide inclusion, aligning their pedagogical practice in an integrated way with reality experienced by their students. In order to carry out this work, which is of a qualitative nature, a bibliographical research was necessary, that is, a detailed research with highly relevant materials, a bibliographic survey, bringing the concepts of the main authors to this theme, with the proposal to deepen, enriching the discussion of the studied theme, through studies and bibliographical references of authors of great expression in the educational area, based on reading and reflection of books, articles and websites, in which this work was used in the production. In the process of choosing the material, there was a significant analysis of everything that was prepared, seeking a better understanding of it, detecting the best references to be applied in the production of the article, taking into account the need for the topic for deaf education. Above all, especially in the curriculum aimed at this issue and at pedagogues. This study provided new knowledge about special and inclusive education in research and practice.